Attention-Weighted Rate Allocation in Free-Viewpoint Television - Scandarolli, Thacio; Queiroz, Ricardo L. de; Florencio, Dinei (IEEE SPS, 2013)
An architecture for free-viewpoint broadcast television transmission is proposed where all the views are transmitted at potentially different qualities and watched by a large number of viewers. The quality (or bit-rate) of each view is controlled by the distribution of viewpoints chosen by the viewers. For example, if most viewers are watching synthetic views in between views n and n+1, those views are allocated more transmission bits than views that are scarcely watched. We developed an attention-weighted bitrate-allocation method that is optimal in the total observer distortion sense. The optimality of the method relies on knowing the viewpoint probability distribution at every moment. Simulation results show that overall transmission rate can be reduced for the same total observed distortion.